2012
DOI: 10.1590/s1517-83822012000200003
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of an Ashbya gossypii mutant for improved riboflavin production

Abstract: The use of the filamentous fungus, Ashbya gossypii, to improve riboflavin production at an industrial scale is described in this paper. A riboflavin overproducing strain was isolated by ultraviolet irradiation. Ten minutes after spore suspensions of A. gossypii were irradiated by ultraviolet light, a survival rate of 5.5% spores was observed, with 10% of the surviving spores giving rise to riboflavin-overproducing mutants. At this time point, a stable mutant of the wild strain was isolated. Riboflavin producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…The medium pH quickly dropped from pH 6.0 on the first day to pH 2.0 at the end of incubation, which had a negative effect on riboflavin production. At pH 2.0 the riboflavin production starts to decrease until has become negligible or absent after 72 h of the incubation time 38 .
Figure 4 Growth and riboflavin production of G.oxydans FBFS97 in fermentation media, the results represent mean values for three shake flasks.
…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The medium pH quickly dropped from pH 6.0 on the first day to pH 2.0 at the end of incubation, which had a negative effect on riboflavin production. At pH 2.0 the riboflavin production starts to decrease until has become negligible or absent after 72 h of the incubation time 38 .
Figure 4 Growth and riboflavin production of G.oxydans FBFS97 in fermentation media, the results represent mean values for three shake flasks.
…”
Section: Resultsmentioning
confidence: 98%
“…The medium pH quickly dropped from pH 6.0 on the first day to pH 2.0 at the end of incubation, which had a negative effect on riboflavin production. At pH 2.0 the riboflavin production starts to decrease until has become negligible or absent after 72 h of the incubation time 38 .…”
Section: Genome Features and Identification Of Riboflavin In The G Omentioning
confidence: 98%
“…The production levels of these bioproducts by other microorganisms are also presented for comparison. likely to be contaminated or degraded by native proteins; 15,16 (d) high genetic tractability, with a rich molecular toolbox available for its manipulation; 2,25 (e) remarkable genomic similarities with the budding yeast S. cerevisiae, which facilitates the transfer of accumulated know-how on this model yeast genetics and cell biology to A. gossypii; 2 (f) ability to grow in cheap waste-derived substrates to high cell densities; [26][27] (g) and demonstrated suitability for use in large-scale industrial fermentation processes. 1,3 While the first heterologous proteins secreted by A. gossypii (endoglucanase I (EGI) and cellobiohydrolase I (CBHI) from Trichoderma reesei) were produced at very low yields, 16 latter on it was found that the expression vector and promoter (from ScPGK1) initially used were inefficient in promoting gene overexpression in A. gossypii.…”
Section: Recombinant Protein Productionmentioning
confidence: 99%
“…10 On the other hand, one important way to lower production costs is by using inexpensive carbon sources and nutrients, preferably from widely available industrial residues. In this sense, the known ability of A. gossypii to grow in some industrial by-products and low-cost oils 2,26,27 may be easily explored. Additionally, the expansion of the carbon source range that A. gossypii can utilize by metabolic engineering (e.g., xylose utilization) may open new perspectives in terms of the raw substrates that may be used in these processes (such as lignocellulosic biomass).…”
Section: Optimization Of Production Conditionsmentioning
confidence: 99%
“…Dentre os fungos,Cheng et al (2011), estudaram a produção de riboflavina por Eremothecium ashbyii, avaliando os efeitos de diferentes fontes de carbono alcançando uma produção máxima de 3107,59 mg/L de riboflavina. Já Suzuki, Fleuri e Macedo (2012) avaliaram a produção de riboflavina por Candida sp, estudando os efeitos de diferentes fontes de carbono e nitrogênio, resultando em uma produção de 105,7 mg/mL de riboflavina Wei et al (2012). estudaram o isolamento de Ashbya gossypii com ultravioleta, gerando uma linhagem mutante capaz de produzir 8,12 g/L de riboflavina, com potencial para aplicação na produção em escala industrial dessa vitamina.A produção microbiológica de biotina foi estudada por El-Refai et al (2010) que demonstraram a eficiência do delineamento experimental multifatorial na produção de biotina por Rhizopus nigricans.…”
unclassified